Exploring student mobility and graduate migration: undergraduate mobility propensities in two economic crisis contexts - Cairns, D. (2017)
This article explores the issue of mobility propensity among undergraduates, focusing on plans for long-term and short-term movement, including migration after the completion of present course of study. We also assess the strength of the relationship between a decision to move abroad and the personal impact of the ongoing economic crisis, using evidence from two recent surveys conducted with students in the capital cities of Portugal and the Republic of Ireland. Results provide an indication of the popularity of moving abroad and identify justifications for seeking an exit, potential destinations and anticipated lengths of stays. Regression analysis further confirms that the crisis is having a significant bearing on mobility decisions among respondents in Portugal but not the Republic of Ireland, with the concluding discussion integrating the main findings into existing debates on international student mobility.